Maconochie's gentlemen : the story of Norfolk Island & the roots of modern prison reform - Morris, Norval, 1923-2004 (Studies in crime and public policy., 2002)
In 1840, Alexander Maconochie, a retired naval captain, became superintendent of two thousand twice-convicted prisoners on Norfolk Island, a thousand miles off the coast of Australia. He transformed the brutal convict settlements into a controlled, stable, and productive environment. This book offers an account of this pioneer in penal reform.